Measurement report: Rapid decline of aerosol absorption coefficient and aerosol optical property effects on radiative forcing in an urban area of Beijing from 2018 to 2021 - Hu, Xinyao; Sun, Junying; Xia, Can; Shen, Xiaojing; Zhang, Yangmei; Liu, Quan; Liu, Zhaodong; Zhang, Sinan; Wang, Jialing; Yu, Aoyuan; Lu, Jiayuan; Liu, Shuo; et al. (Atmospheric chemistry and physics, 2023)
Reliable observations of aerosol optical properties are crucial for quantifying the radiative forcing of climate. The simultaneous measurements of aerosol optical properties at three wavelengths for PM1 and PM10 were conducted in urban Beijing from March 2018 to February 2022. The aerosol absorption coefficient (σab) at 550 nm of PM10 and PM1 decreased by 55.0 % and 53.5 % from 2018 to 2021. The significant reduction in σab may be related to reduced primary emissions caused by effective air pollution control measures. PM2.5 mass concentration decreased by 34.4 % from 2018 to 2021. Single scattering albedo (SSA) increased from 0.89±0.04 for PM10 (0.87±0.05 for PM1) in 2018 to 0.93±0.03 for PM10 (0.91±0.04 for PM1) in 2021. Increasing SSA and decreasing PM2.5 mass concentration suggest that the fraction of absorbing aerosols decreased with improved air quality due to pollution control measures being taken. The annual average submicron absorption ratio (Rab) increased from 86.1 % in 2018 to 89.2 % in 2021, suggesting that fine particles are the main contributors to total PM10 absorption and that the contribution of fine particles to absorption became more important. The absorption Ångström exponent (AAE) in winter decreased from 2018 to 2021, implying a decreasing contribution from brown carbon to light absorption, which may relate to the reduced emissions of biomass burning and coal combustion. During the study period, aerosol radiative forcing efficiency became more negative, mainly influenced by increasing SSA and was −27.0 and −26.2 W m−2 per aerosol optical depth (AOD) for PM10 and PM1 in 2021. Higher σab and PM2.5 mass concentrations were primarily distributed in clusters 4 and 5, transported from the south and the west of Beijing each year. σab and PM2.5 corresponding to clusters 4 and 5 decreased evidently from 2018 to 2021, which may result from the control of source emissions in surrounding regions of Beijing. The 4-year data presented in this study provide critical optical parameters for radiative forcing assessment within two size ranges and are helpful for evaluating the effectiveness of clean air action.